2009
DOI: 10.5424/sjar/2009071-397
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and psycho-sociological quality indexes in greenhouses, Almería (Spain)

Abstract: This study investigates the use of the Labour Economics and Sociology Laboratory of France (LEST) method to analyse work posts among greenhouse workers in the Almería region of south-eastern Spain. The aim is to improve the health of the labourers. Data were gathered from 110 greenhouses, 73 of the Almería parral plano type and 37 raspa and amagado. Crops studied were 63 greenhouses of tomatoes, 31 of watermelons, and 16 of courgette, examining the physical environment, physical load, psycho-social aspects, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
15
0
3
Order By: Relevance
“…However, they are more negative for older people than those obtained by Bernhardt et al (1999) who reported a 38% of fatal injuries in the group of 65 and older but less negative results for young people. Callejón Ferre et al (2009) concluded that more information on work risks would be helpful. Table 5 displays the causes of the 388 fatal accidents investigated in this research.…”
Section: Resultsmentioning
confidence: 99%
“…However, they are more negative for older people than those obtained by Bernhardt et al (1999) who reported a 38% of fatal injuries in the group of 65 and older but less negative results for young people. Callejón Ferre et al (2009) concluded that more information on work risks would be helpful. Table 5 displays the causes of the 388 fatal accidents investigated in this research.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies evaluated the ergonomic and psychosociological conditions of farm workers in different crops using the LEST (Labour Economics and Industrial Sociology) method [57], and they suggested improvements and more specific ergonomic studies [58,59].…”
Section: Previous Studies Of Intensive Agriculture In Greenhouses In mentioning
confidence: 99%
“…Este resultado permite aumentar la disponibilidad de tiempo, evitando la ejecución de tareas forzadas con estrés, que como relata Callejón-Ferre, et al, (2009) (29) disminuyen la atención y aumentan la fatiga del trabajador, reduciendo de esta forma la siniestralidad asociada.…”
Section: Discussionunclassified
“…En la actualidad son muchas las investigaciones sobre seguridad laboral en construcción, abordando preferentemente las edificaciones y construcciones industriales (16)(17)(18)(19)(20)(21), siendo escasos los estudios específicos sobre construcción de invernaderos (22)(23), limitándose las publicaciones existentes a citar metodologías y describir tipologías constructivas (24)(25)(26)(27)(28), aunque sí se hace perceptible, la presencia de estudios sobre ergonomía en entornos laborales de invernaderos (29).…”
Section: Introductionunclassified